Strategi Humas Badan Narkotika Nasional Jawa Barat dalam Mensosialisasikan Program Rehabilitasi - Novianti, Silvia; Abidin, Yusuf Zaenal; Muchtar, Khoiruddin (Jurnal InterAct, 2020)
This study aimed to determine the Public Relations strategy of Badan Narkotika Nasional West Java Province in disseminating the rehabilitation program. This study discusses the rehabilitation programs socialization related to data collection, planning and programming, implementation, and evaluation. This study used a qualitative descriptive analysis method and the four-step public relations concept with a qualitative approach and constructivism paradigm. Data collection was carried out through interviews and observations. The results showed that the Public Relations strategy of BNN West Java Province in socializing the rehabilitation program was carried out by searching for data using survey methods, planning and programming by determining objectives, determining targets, determining messages and determining time, selecting implementers, and the use of media used, and evaluating with see success in socializing.